Automatic price scanning system / Fahmi Nazreen Zakuan ... [et al.] - Zakuan, Fahmi Nazreen; Rosli, Anis Diyana; Ismail, Nurlida (2021)
This paper proposed an automatic price scanning system to be used in supermarket to overcome the drawback of conventional system i.e manual scanner. The existing method for price scanning is by using the barcode scanner which required the cashier to scan the items manually before the price is displayed on the monitor. This method is inconvenient as the cashier has multiple tasks to be performed concurrently such as scanning the items, packaging the items, and processing the payment which can lead to longer waiting time for the customer. The mentioned issues can be accommodated by the use of Automatic Price Scanning System. This proposed system offers automatic items detection via the use of an infrared (IR) sensor which will operate the conveyor upon the item detection. The items will then move towards the cashier and stop at the Radio frequency Identification (RFID) reader for further action i.e scanning the price. This system employs RFID reader to scan the tags attached to the items prior to data processing by the Arduino Mega 2560. The Arduino will then command the Liquid Crystal Display (LCD) to display the total price of the items. The proposed system was tested with two different types of RFID tags where each of them is assigned to dissimilar value of price. The accuracy of the proposed development has been assessed in terms of movement of conveyor and price detection with an average of 86.67% accuracy. With this reliable measurement, the automatic price scanning system enables cashier to optimize their task. Consequently, the waiting time for the customers can be minimized.